Career information and guidance and counselling - Ramesh Chandra (Delhi : Isha books)
Choosing a career is an important decision in one,s life. Today, career information and guidance and counselling has become a specialised field. And i is not a single field; it is well-branched out. The book gives one detailed knowledge about the various dimensions of career information and counselling. It emphasised on the need of guidance practitioners. the book also brings out the benefits of workplace counselling and psychological and social needs of parents. Importance of well-organised career information, guidance and counselling services, both to education systems as well as job market,emphasised in the book. The social services can bring about a major improvement in individual decision making.
includes bibliographical references and index.
Keywords: Career -- Counselling; Career -- Guidance